2019
DOI: 10.1111/fare.12404
|View full text |Cite
|
Sign up to set email alerts
|

Is Breaking Up Hard to Do? Exploring Emerging Adults' Perceived Abilities to End Romantic Relationships

Abstract: Objective To explore emerging adults' beliefs about their ability to end romantic relationships and to identify demographic, personality, and romantic experience factors associated with breakup beliefs. Background Although, ending relationships is a key component of emerging adult romantic development, research suggests that breakups tend to be protracted and painful. Little is known about what individual skills might be relevant in making breakups smoother for both members of a couple. Method Using a cross‐se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…Finally, relationship education curricula should include information about the steps and processes involved in ending romantic partnerships. In a recent study of emerging adults, Beckmeyer and Jamison (2019) found that approximately 25% to 30% of emerging adults perceive they are unable to carry out specific breakup tasks, such as identifying when to break up, following through with a breakup, accepting a partner wanting to break up, and not delaying breakups. In the present study, the primary barriers seemed to be knowing when to break up and not delaying the breakup, particularly when unexpected events happened that made the timing seem inopportune.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, relationship education curricula should include information about the steps and processes involved in ending romantic partnerships. In a recent study of emerging adults, Beckmeyer and Jamison (2019) found that approximately 25% to 30% of emerging adults perceive they are unable to carry out specific breakup tasks, such as identifying when to break up, following through with a breakup, accepting a partner wanting to break up, and not delaying breakups. In the present study, the primary barriers seemed to be knowing when to break up and not delaying the breakup, particularly when unexpected events happened that made the timing seem inopportune.…”
Section: Discussionmentioning
confidence: 99%
“…Emerging adults who see their exploratory relationships as potential long-term unions may benefit from resources and programs that help them communicate relational goals and expectations to their partners. Those who do not see long-term potential for their relationships may benefit from relationship education resources focused on determining when and how to end their relationships when they no longer meeting their needs (Beckmeyer & Jamison, 2019). Emerging adults in stuck or high-intensity relationships may need therapy in addition to relationship education.…”
Section: Implications For Relationship Educationmentioning
confidence: 99%
“…Several studies hypothesized that people can effectively adjust to a loss when they reorganize their attachment system and no longer take into account the former partner as a “secure base” (Feeney and Monin, 2016 ; Guzmán-González et al, 2019 ; Kluwer et al, 2020 ), but less is known of the initial phases of the adjustment process, in terms of sociodemographic variables and attachment styles (Saffrey and Ehrenberg, 2007 ). Aspects, such as perceived self-efficacy, education, current relationship status, and romantic attachment styles are seen as key factors in the dissolution of a previous romantic involvement (Amato and Previti, 2003 ; Beckmeyer and Jamison, 2020 ; Karney, 2021 ).…”
Section: Introductionmentioning
confidence: 99%